2022
DOI: 10.3389/fnut.2022.940514
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Cancer, Government Strategic Policies, and Challenges in Pakistan: A Comprehensive Review

Abstract: Cancer is a severe condition characterized by uncontrolled cell division and increasing reported mortality and diagnostic cases. In 2040, an estimated 28.4 million cancer cases are expected to happen globally. In 2020, an estimated 19.3 million new cancer cases (18.1 million excluding non-melanoma skin cancer) had been diagnosed worldwide, with around 10.0 million cancer deaths. Breast cancer cases have increased by 2.26 million, lung cancer by 2.21 million, stomach by 1.089 million, liver by 0.96 million, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 172 publications
1
27
0
Order By: Relevance
“…Similar results among Afghans have been reported by others (9,10). Interestingly, these numbers are comparable to the cancer statistics among Pakistanis and Iranians (10)(11)(12). A recent study of Afghan oesophageal cancer patients has suggested that living in a rural area, illiteracy, consuming oral snuff, drinking hot tea, lack of physical exercise, modest consumption of fruit, and positive family history of cancer were significantly associated with the development of oesophageal cancer (13).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results among Afghans have been reported by others (9,10). Interestingly, these numbers are comparable to the cancer statistics among Pakistanis and Iranians (10)(11)(12). A recent study of Afghan oesophageal cancer patients has suggested that living in a rural area, illiteracy, consuming oral snuff, drinking hot tea, lack of physical exercise, modest consumption of fruit, and positive family history of cancer were significantly associated with the development of oesophageal cancer (13).…”
Section: Discussionsupporting
confidence: 90%
“…The overproduction of ROS may be further exacerbated by the redox-sensitive transcription factors, including NF-kB and activator protein (AP)-1, which are activated by ROS and produce many pro-inflammatory cytokines ( 27 ). It causes a cycle that breeds a variety of illnesses, including insulin resistance, T2DM, atherosclerosis, and cancer, all referred to as MS ( 27 , 43 ).…”
Section: Relationship Between Ox-ldl and Metabolic Disordersmentioning
confidence: 99%
“…In recent years, the incidence rate of cancer has increased year by year, which has placed a serious burden on society ( Ali et al, 2022 ). At present, cancer treatment mainly includes chemotherapy, surgery, radiotherapy, targeted therapy and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%